The Role of Mothers in Instilling Islamic Education Values in Children in the Digital Era - Dian Annisa; Tobroni Tobroni; Fahrudin Muhklis (At-Ta'lim : Media Informasi Pendidikan Islam, 2023)
Abstract: The Role of the Mothers in Instilling Islamic Education Values in Children in the Digital Age Era. Mothers have an important role in children's education, especially in religious education, and are required to be more active and creative in presenting various ways of educating children by integrating technological devices with good education. The purpose of this study is to (1) Describe the position of mothers in Islamic religious education in the digital era, (2) Describe the parenting patterns applied in children's education in the digital era, and (3) Examine the effectiveness of maternal parenting in religious education. This research is qualitative research with a case study approach. The subject selection used Snowball sampling. the subjects amounted to ten mothers with different educational and economic backgrounds. The research location was conducted in Rato Village, precisely in NTB Province. Data collection was carried out by interview, observation, and documentation methods. The results showed that Rato village mothers can understand the position of mothers well. Mother's parenting in the digital era is still not maximally implemented due to a lack of digital literacy. The level of effectiveness of parenting patterns of Rato village mothers in religious education in the digital era is still not said to be effective. Abstrak: Peran Ibu dalam Menanamkan Nilai-nilai Pendidikan Agama Islam pada Anak di Era DigitalIbu memiliki peran penting dalam pendidikan anak, terutama dalam pendidikan agama dituntut untuk lebih aktif dan kreatif dalam menghadirkan berbagai cara mendidik anak dengan mengintegrasikan perangkat teknologi dengan pendidikan yang baik. Tujuan penelitian ini ialah untuk (1) Mendeskripsikan kedudukan ibu dalam pendidikan agama islam di era digital, (2) Mendeskripsikan pola asuh yang diterapkan dalam pendidikan anak di era digital, dan (3) Mengkaji keefektifan pola asuh ibu dalam pendidikan agama. Penelitian ini merupakan penelitian kualitatif dengan pendekatan studi kasus. Pemilihan subjek menggunakan Snowball sampling. subjek berjumlah sepuluh ibu-ibu dengan latar belakang pendidikan dan ekonomi yang berbeda-beda. Lokasi penelitian dilakukan di Desa Rato tepatnya di Provinsi NTB. Pengumpulan data dilakukan dengan metode wawancara, obsevasi dan dokumentasi. Hasil penelitian menunjukkan bahwa ibu-ibu desa Rato dapat memahami kedudukan ibu dengan baik. Pola asuh ibu di era digital masih belum maksimal diterapkan karena kurangnya literasi digital. Tingkat keefektifan pola asuh ibu-ibu desa Rato dalam pendidikan agama di era digital masih belum dikatakan efektif